Prediksi Kebutuhan Data Mahasiswa Untuk Kuliah Daring Kondisi Covid-19 Di Jurusan Teknik Elektro Universitas Mataram: Prediction of Student Data Needs for Online Lectures Covid-19 Conditions in the Department of Electrical Engineering, University of Mataram - Made Sutha yadnya; Ni Luh Sinar Ayu Ratna Dewi; Sudi Maryanto Al Sasongko; Rosmaliati Rosmaliati; Abdulah Zainuddin (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2022)
In the covid-19 condition, lectures at the Department of Electrical Engineering, Mataram University changed from a face-to-face process to via the Internet. T here will be a very sharp increase in demand. The use of data initially provided by the University of Mataram using a free hotspot network turned into a burden on lecturers and students. This research was conducted by sampling, general compulsory subjects, compulsory electrical courses, and compulsory expertise subjects. The distribution of variations of students domiciled in the City of Mataram and the other place coverage Lombok Island, within NTB and outside NTB. The results obtained are as follows: students who still survive in Mataram City are 17% (10.5 GB), Lombok Island 48% (8.1 GB), outside Lonbok Island 27% (4.8 GB), and outside NTB 8% (15 GB). Keyword : covid-19; lectures; online